2021
DOI: 10.3390/ijerph181910111
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Labor, Burnout, Medical Error, and Turnover Intention among South Korean Nursing Staff in a University Hospital Setting

Abstract: Nurses are vulnerable to mental health challenges, including burnout, as they are exposed to adverse job conditions such as high workload. The mental health of this population can relate not only to individual well-being but also to patient safety outcomes. Therefore, there is a need for a mental health improvement strategy that targets this population. This cross-sectional survey study investigates emotional labor, burnout, turnover intention, and medical error levels among 117 nursing staff members in a Sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 27 publications
3
16
0
Order By: Relevance
“…Gender and age differences in personal discrimination experience, burnout, and job stress among physiotherapists and occupational therapists are examined in South Korea [132]. Nurses in South Korea are further studied with respect to emotional labor, burnout, turnover intention, and medical error levels within the previous six months [133]. Healthcare workers are also the focus of another study in Japan [134], which concludes that the number of physical symptoms perceived are positively related to burnout scores.…”
Section: Special Issue On "Occupational Stress and Health: Psychologi...mentioning
confidence: 99%
“…Gender and age differences in personal discrimination experience, burnout, and job stress among physiotherapists and occupational therapists are examined in South Korea [132]. Nurses in South Korea are further studied with respect to emotional labor, burnout, turnover intention, and medical error levels within the previous six months [133]. Healthcare workers are also the focus of another study in Japan [134], which concludes that the number of physical symptoms perceived are positively related to burnout scores.…”
Section: Special Issue On "Occupational Stress and Health: Psychologi...mentioning
confidence: 99%
“…The continuous burnout among nurses may deteriorate their health and specifically their mental health which may affect their performance at work (Hamed et al., 2020 ; Zeng et al., 2020 ). That is, burnout has strongly been associated with reduced job performance, poor quality of care, poor patient safety, adverse events, patient negative experience, medical errors, infections, patient falls and intention to leave (Al Sabei et al., 2020 ; Dall'Ora et al., 2020 ; Kwon et al., 2021 ) This leaves a huge financial burden and serious administrative challenges for the health authorities (managers and directors). For instance, the estimated financial cost for burnout‐related turnover among US physicians and nurses was $17 and $14 billion, respectively, per annum (National Taskforce for Humanity in Healthcare, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Emotional labor has both positive and negative effects on work. Previous studies on nurses’ emotional labor paid more attention to the negative impact of emotional labor, such as depression, emotional exhaustion and job burnout [ 44 , 45 ] But the positive effects of emotional labor, which was beneficial to nurses’ work engagement, had also been reported [ 18 ]. Our study found that emotional labor could promote the development of nurses’ professional values.…”
Section: Discussionmentioning
confidence: 99%